2019
DOI: 10.1088/1742-6596/1276/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of Stagnation Temperature and Overall Heat Transfer Coefficient of Flat Receiver for Solar Parabolic Dish Concentrator System

Abstract: The parabolic dish concentrator is one of the most efficient technologies to convert direct beam radiation into thermal energy for steam and power generation. The parabolic dish concentrates direct beam radiation from the sun on to a receiver at the focal point. The receiver plays a major role to transform the reflected solar radiation into thermal energy. The conversion efficiency of the dish is severely influenced by imperfection of the dish collector such as the contour of parabola, size of the facets align… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Another alternative, as defined in ref. [18], is using butane gas to achieve heat transfer. The outcomes showed that using butane gas for transferring heat will restrict the max temperature in the system's solar loop to 120 C or less, allowing for better collector efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Another alternative, as defined in ref. [18], is using butane gas to achieve heat transfer. The outcomes showed that using butane gas for transferring heat will restrict the max temperature in the system's solar loop to 120 C or less, allowing for better collector efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several methods were tested and applied to control inactiveness in the experiential reg system; the appropriate solution must be simple to execute, inexpensive, and run continuously without any technical issues [13][14][15][16][17][18][19][20][21].…”
Section: Attempts To Resolve the Issue Of Inactivenessmentioning
confidence: 99%
See 3 more Smart Citations